Mechanistic insights into allosteric regulation of the A2A adenosine G protein-coupled receptor by physiological cations - Ye, Libin; Neale, Chris; Sljoka, Adnan; Lyda, Brent; Pichugin, Dmitry; Tsuchimura, Nobuyuki; Larda, Sacha T.; Pomès, Régis; García, Angel E.; Ernst, Oliver P.; Sunahara, Roger K.; Prosser, R. Scott (Nature communications, 2018)
Cations play key roles in regulating G-protein-coupled receptors (GPCRs), although their mechanisms are poorly understood. Here, 19 F NMR is used to delineate the effects of cations on functional states of the adenosine A 2A GPCR. While Na + reinforces an inactive ensemble and a partial-agonist stabilized state, Ca 2+ and Mg 2+ shift the equilibrium toward active states. Positive allosteric effects of divalent cations are more pronounced with agonist and a G-protein-derived peptide. In cell membranes, divalent cations enhance both the affinity and fraction of the high affinity agonist-bound state. Molecular dynamics simulations suggest high concentrations of divalent cations bridge specific extracellular acidic residues, bringing TM5 and TM6 together at the extracellular surface and allosterically driving open the G-protein-binding cleft as shown by rigidity-transmission allostery theory. An understanding of cation allostery should enable the design of allosteric agents and enhance our understanding of GPCR regulation in the cellular milieu. G protein-coupled receptors (GPCRs) are membrane receptors and are important drug targets, whose regulation by cations is poorly understood. Here authors use NMR to elucidate effects of cations on functional states of the GPCR, adenosine A 2A receptor (A 2A R).